LEARNING DESIGN FOR INTRODUCING - Jakfar, Muhammad; Fardah, Dini Kinati (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
Introducing the Euler’s number, or symbolized as e, is often done formally by teachers of the course of differential calculus at the college level. This makes students not really familiar with this number. In fact, the concept of this number is very often used or involved in mathematics and mathematics education study programs. For this reason, this study aims to provide alternative learning to introduce the Euler’s number to students using a geometric approach. This type of research is design research using ADDIE model, which has reached the design stage. The results of this study are the result of the analysis stage, which consisted of learner analysis, instructional analysis, and instructional objective, and the results of the design stage, which emerge the learning phase to guide the students to construct the definition of Euler’s number geometrically which consisted of six steps, namely: 1) sketching the exponential function; 2) sketching the logarithmic function; 3) answering the problems given regarding the function of the exponent and tangent to the function with the help of illustrations provided through the GeoGebra application; 4)through the steps to find the number e given, students are asked to explain the reasons that underlie the action of each step; 5) determining the value of the number e through the illustration in the GeoGebra application; and 6) constructing the definition the Euler’s number geometrically.